Comportamentos ergonômicos no atendimento odontológico: Estudo e recomendações para cirurgiões-dentistas - Mendes, Ayonara Dayane Leal (2019)
The dental surgeon is considered a vulnerable professional to several risks, in special, associated with ergonomic factors. Since that are exposed to physical wear related to labour, becomes predisposed in the health impacts, as a larger in musculoskeletal incidence related to labour (MIRLs). The aim this is search is proposed about ergonomic behaviour in dental surgeon, apply it to similar case, as well as suggest behaviour recommendation to this professional. First step this search will be the literature review, that subsidize the second and third step, to be constituted respectively through creation protocol of the study and guide recommendation about ergonomic behaviour in dental care. The ergonomic design of the Odonatological office is a basic requirement to propose good conditions of the labour to dental surgeon, however, the needs this is professionals goes beyond. Likewise, the targeted researches to analysis in associated about physical environment, professional behaviour are essential, because help this occupational in improvement their health through ergonomic behaviour suitable. For this reason, will contribute to reduction of the musculoskeletal pain able to affect as life quality and income at work, as well as occurrences of the physical diseases and psychic in dental surgeon.